Synthesis of Novel Chitosan Derivatives - Li, R.C. (Asian Journal of Chemistry, 2011)
Novel chitosan derivatives 2-[4-(2-fluorobenzylideneamino)pyridyl]acetyl chitosan chloride (FBPACS), 2-[4-(2-chlorobenzylideneamino)-pyridyl]acetyl chitosan chloride (CBPACS), 2- [4-(2-bromobenzylideneamino)pyridyl]acetyl chitosan chloride (BBPACS), 2-[4-(2,4- dichlorobenzylideneamino)pyridyl]acetyl chitosan chloride (DCBPACS) and 2-[4-(2,4- difluorobenzylideneamino)pyridyl]acetyl chitosan chloride (DFBPACS) were prepared. The structures of the derivatives were confirmed by Fourier transform infrared and 13C nuclear magnetic resonance. These novel chitosan derivatives were expected to have potent biological activities due to the halo-benzaldehyde condensation 4-aminopyridine Schiff base structure in their molecules.